Perspectives on imitation : from neuroscience to social science. - Hurley, S. L. (Susan L.); Chater, Nick (MIT Press, 2005)
A state-of-the-art view of imitation from leading researchers in neuroscience and brain imaging, animal and developmental psychology, primatology, ethology, philosophy, anthropology, media studies, economics, sociology, education, and law. Leading researchers across a range of disciplines provide a state-of-the-art view of imitation, integrating the latest findings and theories with reviews of seminal work, and revealing why imitation is a topic of such intense current scientific interest.
Keywords: Imitation.; Learning in animals.; Social psychology.; Animal behavior.; Imitative Behavior; Psychology, Social; Behavior, Animal; Human Development; Imitation (Psychologie); Apprentissage chez les animaux.; Psychologie sociale.; Animaux -- Mœurs et comportement.; social psychology.; PSYCHOLOGY -- Social Psychology.; Animal behavior; Imitation; Learning in animals; Social psychology; NEUROSCIENCE/General